1993
DOI: 10.1002/esp.3290180905
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of river bank erosion and lateral channel change: A review

Abstract: A detailed review and chronological survey is presented of the various techniques which have been used for the measurement of river bank erosion and channel change. The techniques are classified according to the time scales involved (long, intermediate and short) and each is discussed with respect to accuracy and repeatability. The methods covered include sedimentological evidence, botanical evidence, historical sources, planimetric resurvey, repeated crossprofiling, erosion pins and terrestrial photogrammetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
278
0
6

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 358 publications
(288 citation statements)
references
References 115 publications
4
278
0
6
Order By: Relevance
“…For the purposes of this paper we focus on the first monitoring period, between October and December 2003. Bank retreat during this period was monitored by periodic topographic surveys, combined with a network of vertical pins at a total of 27 sections distributed along the bank top for prompt baseline resurvey using perpendicular offsets [Lawler, 1993] immediately after each flow event, and horizontal erosion pins along 6 representative bank profiles. Bank retreat observed during the study period is reported in Figure 2.…”
Section: Study Site Descriptionmentioning
confidence: 99%
“…For the purposes of this paper we focus on the first monitoring period, between October and December 2003. Bank retreat during this period was monitored by periodic topographic surveys, combined with a network of vertical pins at a total of 27 sections distributed along the bank top for prompt baseline resurvey using perpendicular offsets [Lawler, 1993] immediately after each flow event, and horizontal erosion pins along 6 representative bank profiles. Bank retreat observed during the study period is reported in Figure 2.…”
Section: Study Site Descriptionmentioning
confidence: 99%
“…Notable exceptions to this trend include some work that has sought to quantify entrainment thresholds and process rates (e.g., Lawler et al, 1997a;Simon et al, 2000;Dapporto, 2001). The role of weathering as a significant agent of erosion has also started to be recognised (e.g., Lawler, 1993;Prosser et al, 2000;Couper and Maddock, 2001), both in headwater reaches (where weathering may be the dominant mechanism by which sediment is removed from the bank face) and, elsewhere, as a mechanism for enhancing bank erodibility and promoting fluvial erosion. Fig.…”
Section: Gbr1mentioning
confidence: 99%
“…Fluvial erosion is defined as the removal of bank material by the action of hydraulic forces, although it generally occurs in combination with weathering processes that prepare bank sediments for erosion by enhancing their erodibility (Hooke, 1980;Thorne, 1982;Lawler, 1993; ASCE Task Committee on Hydraulics, Bank Mechanics, and Modeling of River Width Adjustment, 1998;Prosser et al, 2000;Couper and Maddock, 2001). Relative to mass failure, fluvial erosion is, at the scale of the flow event and once the critical entrainment threshold has been exceeded, a quasi-continuous process, with the volume of sediment delivered by fluvial erosion dependent on the duration of the competent flow.…”
Section: Modelling Fluvial Erosionmentioning
confidence: 99%
See 2 more Smart Citations